Effect of hydrogen on the creep of the ultrafine-grained zirconium Zr–1Nb alloy at 673 K; International Journal of Hydrogen Energy; Vol. 42, iss. 35 - Grabovetskaya G. P. Galina Petrovna (2017, 2017)
Title screen